Pengembangan Wisata Halal di Kawasan Danau Toba: Persepsi Pelaku Usaha Wisata Hotel dan Restoran - Sidabutar, Anggun; Vany Octaviany (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The people of Lake Toba are dominated by the Batak tribe who adhere to Christian and Catholic beliefs. The livelihoods of the people of Lake Toba are also dominated by farming, fishing and business. Where the community plays an important role in Lake Toba tourism, such as being hoteliers, restaurants and managers of tourist attractions. Lake Toba was designed as one of the halal tourist destinations in Indonesia, but rejection occurred among the community, especially tourism managers in the Lake Toba area. Rejection occurred because people thought that it was against the traditions and culture of the Batak tribe that had existed for generations. The aim of this research is to determine the perceptions of non-Islamic business actors in developing halal tourism in Lake Toba. The research methodology used in this study is a quantitative approach by distributing questionnaires and using factor analysis. The sample used is a saturated sample where the sample is business managers in the Lake Toba area. The results of the research to be aimed at are looking at the perceptions and readiness of hotel and restaurant business tourism doer towards the development of halal tourism in the Lake Toba area.